Synergistic Activity of Niclosamide in Combination With Colistin Against Colistin-Susceptible and Colistin-Resistant Acinetobacter baumannii and Klebsiella pneumoniae - Ayerbe-Algaba, Rafael; Gil-Marqués, María Luisa; Jiménez-Mejías, Manuel Enrique; Sánchez-Encinales, Viviana; Parra-Millán, Raquel; Pachón-Ibáñez, María Eugenia; Pachón, Jerónimo; Smani, Younes (Frontiers in Cellular and Infection Microbiology, 2018)
Colistin is among the few antibiotics effective against multidrug-resistant Acinetobacter baumannii and Klebsiella pneumoniae clinical isolates. However, in the last few years, colistin-resistant A. baumannii and K. pneumoniae strains have emerged. Therefore, combination therapies, between colistin and other old drugs, restoring the activity of colistin are required. The main objective of this study was to analyse the activity of niclosamide, an anthelmintic drug, in combination with colistin against colistin-susceptible (Col-S) and colistin-resistant (Col-R) A. baumannii and K. pneumoniae. The MIC were determined by microdilution assay and the time-kill curves were performed. The zeta potential of Col-S and Col-R of A. baumannii and K. pneumoniae in presence of niclosamide was assessed. Niclosamide in combination with colistin showed improved activity against Col-S and Col-R A. baumannii and K. pneumoniae. Time-killing curves showed synergic activity between niclosamide and colistin against Col-S and Col-R A. baumannii and K. pneumoniae, especially when niclosamide or colistin was added for second time at 4 h of the 24 h killing curve. Col-R A. baumannii and K. pneumoniae in presence of niclosamide exhibited a greater negative charge (-34.95 ± 0.35 mV and -38.85 ± 0.92 mV; P<0.05) than Col-R A. baumannii and K. pneumoniae in absence of niclosamide (-26.85 ± 3.65 mV and -35.27 ± 0.72 mV). These data suggest that niclosamide might be combined with colistin, being a potential alternative for treatment of Col-R Gram-negative bacilli infections.